(untitled) (Web of Teachers: Inderscience Research, 2025)
The article considers the basic definitions and principles of using evolutionary methods, in particular genetic programming, in the optimization and automated design of web interfaces. Existing approaches to the use of evolutionary algorithms to search for new options for the design of web pages are analyzed, and directions for further development of this area are described. Special attention is paid to local search methods and tree-like representation of HTML code as a chromosome. Based on the analysis, a conceptual hypothesis is formulated about the possibility of developing an information system that creates new layouts of web design using evolutionary methods.